Systems resilience assessments: a review, framework and metrics. Issue 2 (17th January 2022) - Cheng, Yao; Elsayed, Elsayed A.; Huang, Zhiyi
Abstract : The past several decades have witnessed an increasing number of natural and manmade hazards with a dramatic impact on the normal operations of the society. The occurrences of these hazards manifest a growing trend of uncertainty. Assessing the performance of systems under such hazards is a salient concern of researchers and practitioners. The notion of 'resilience' has been proposed and popularised to characterise system performance deterioration and restoration due to different hazards and threats. Substantial effort has been devoted to quantify and describe resilience from different perspectives. However, there is no generic metric for assessing the resilience of different systems under different hazards. This paper provides a review of existing approaches that quantitatively assess resilience, along with their applicable scenarios and limitations. New general and generic resilience metrics for systems with multimodal performance are proposed. Opportunities for multi-hazard resilience modelling and enhancements are presented.